Rapidly Polymerizing Click Hydrogel Provides Localized Delivery of rhBMP2 to Promote Bone Formation - D. Joshua Cohen; Thomas W. Jacobs; D. Scott Wilson; Michael C. Mancini; Christine Van Duyn; Zvi Schwartz; Barbara D. Boyan (Pharmacology Research & Perspectives)
ABSTRACT Delivery of bioactive agents to achieve tissue regeneration at targeted sites with minimal side effects requires the use of biodegradable carriers and sustained release of the therapeutic at appropriate concentrations. We developed a copper‐free polyethylene glycol‐based click hydrogel to deliver bone morphogenetic protein‐2 (BMP2), a potent regulator for bone regeneration that is currently delivered to orthotopic sites using an absorbable collagen sponge, leading to a burst release of BMP2, potentially causing ectopic bone formation. In contrast, the hydrogel is delivered as a liquid, conforming to the contours of treatment sites, polymerizing rapidly at body temperature without generating heat, exhibiting minimal swelling after gelation, and releasing its payload as it degrades. We assessed the safety and effectiveness of BMP2 delivery in vitro and in mouse cranial defects in vivo, comparing it to BMP2 delivered via a collagen sponge. No toxicity was observed in vitro or systemically, nor was there allergic sensitization caused by the hydrogel in rabbits. Released BMP2 increased the production of osteogenic markers in vitro. Hydrogel + BMP2 caused equivalent defect closure and total bone growth compared to collagen + BMP2; however, there was more vascularization within the defect but less bone growth outside of the defect on the calvaria for hydrogel + BMP2 compared to collagen + BMP2. In conclusion, the click hydrogels used in this study are safe and effective for administering BMP2 with fewer undesired off‐target effects and high potential to be used with BMP2 for bone regeneration, supporting the use of click chemistry hydrogels to deliver bioactive agents to treatment sites safely and effectively.